Evaluasi Desain Geometrik Jalan terhadap Keselamatan Lalu Lintas Menggunakan Metode EAN–UCL - Nazwa Tiara Herdiani; Ida Farida (Jurnal Konstruksi, 2026)
The Sirnajaya–Papandayan road segment in Cisurupan District, Garut Regency, serves as a primary access route to mountainous tourist areas and is characterized by winding alignments, steep ascents, and sharp descents. These characteristics, combined with limited road width, pavement deterioration, and inadequate safety facilities, make this segment highly prone to traffic accidents. This study aims to analyze the geometric conditions of the road, evaluate their influence on accident rates, and formulate improvement recommendations to enhance road user safety. The research methodology includes surveys of existing conditions, geometric road measurements, accident analysis using the Equivalent Accident Number (EAN) and Upper Control Limit (UCL) methods, and evaluation based on the 2021 Bina Marga geometric design standards. The analysis results indicate the presence of sharp curves with small radii that generate high EAN values, namely 256 for horizontal curve 1 and 288 for horizontal curve 2. In terms of vertical alignment, the segments at STA 0+410–0+420 recorded an EAN value of 15 and STA 0+460–0+470 recorded a value of 12; both exceed the threshold and are classified as black spots. Furthermore, several segments exhibit gradients exceeding 20%, far surpassing the 10% maximum specified by the 2021 Bina Marga standard for collector roads in mountainous areas. Combined with pavement damage and insufficient warning signage, these conditions significantly increase the risk of traffic accidents. In conclusion, improvements are required through the redesign of horizontal and vertical alignments, pavement rehabilitation, and the installation of warning signs, road markings, guardrails, and street lighting. This study provides a scientific basis for road planning and safety enhancement in mountainous regions and can serve as a reference for relevant authorities in addressing road segments with similar characteristics.